My Math Forum How to solve for f(x)

 Elementary Math Fractions, Percentages, Word Problems, Equations, Inequations, Factorization, Expansion

 June 17th, 2018, 10:58 AM #1 Senior Member   Joined: Dec 2015 From: iPhone Posts: 387 Thanks: 61 How to solve for f(x) Solve the equation, find the function f(x), where $\displaystyle f^{-1}(x)$ is inverse of f(x), $\displaystyle f(x)=f^{-1}(x)$ Last edited by skipjack; June 17th, 2018 at 10:13 PM.
 June 17th, 2018, 11:53 AM #2 Math Team   Joined: Jan 2015 From: Alabama Posts: 3,261 Thanks: 896 There is no single answer- there are many functions that are there own inverse. One obvious one is f(x)= x. Another is f(x)= 1/x.
 June 17th, 2018, 12:53 PM #3 Senior Member   Joined: Aug 2012 Posts: 2,157 Thanks: 631 $f(x) = -x$, which works in the real or complex numbers. $f(z) = \overline{z}$, the complex conjugate of $z$.
 June 18th, 2018, 12:39 AM #4 Global Moderator   Joined: Dec 2006 Posts: 20,285 Thanks: 1967 $\displaystyle f(z) = \frac{a - bz}{b - cz}$, where $a$, $b$ and $c$ are constants that don't satisfy $ac = b^2\!$, and $z$ doesn't satisfy $b - cz = 0$.
 June 19th, 2018, 09:51 AM #5 Senior Member   Joined: Dec 2015 From: iPhone Posts: 387 Thanks: 61 I post my work below: $\displaystyle f(x)=f^{-1}f^{-1}(x)=f^{-1}(x)$ $\displaystyle f_1 ^{-1}(x)=x=f_1 (x) \; \;$ and $\displaystyle \; \; f_2 ^{-1}(x)=x$ so we got first solution $\displaystyle f_1 (x)=x$ Now I don't understand how to get the second solution $\displaystyle y=\frac{1}{x}$ from $\displaystyle f_2 ^{-1} (x) =x$ Last edited by skipjack; June 19th, 2018 at 10:13 AM.
 June 19th, 2018, 10:39 AM #6 Global Moderator   Joined: Dec 2006 Posts: 20,285 Thanks: 1967 Your first line, $f(x)=f^{-1}f^{-1}(x)=f^{-1}(x)$, isn't a consequence of the given information. The given information implies that when the function is nested to an even depth, the result simplifies to $x$, and that when the function is nested to an odd depth, the result simplifies to $f(x)$.
 June 21st, 2018, 04:22 AM #7 Senior Member   Joined: Dec 2015 From: iPhone Posts: 387 Thanks: 61 I see but let me explain below : Use $\displaystyle f(x)=f^{-1} f^{-1} (x)$ so equation now is $\displaystyle f^{-1}(x)=f^{-1} f^{-1} (x)$ or $\displaystyle f^{-1}(x)=x$ From the system of equations $\displaystyle \begin{cases} f(f^{-1} (x) )=f(x) \\ f(x)=f^{-1} (x) \end{cases} \Rightarrow f(f^{-1} (x))=f^{-1}(x)$ For $\displaystyle f^{-1}(x)=T$ then $\displaystyle f(t)=t$ which is the first solution The second solution $\displaystyle y=1/x$ will take long write so im not posting it
June 21st, 2018, 05:53 AM   #8
Senior Member

Joined: Apr 2014
From: Glasgow

Posts: 2,135
Thanks: 720

Math Focus: Physics, mathematical modelling, numerical and computational solutions
Quote:
 Originally Posted by idontknow How to solve for f(x) Solve the equation
Done!

 Tags solve

 Thread Tools Display Modes Linear Mode

 Similar Threads Thread Thread Starter Forum Replies Last Post gen_shao Algebra 12 November 2nd, 2014 07:11 AM

 Contact - Home - Forums - Cryptocurrency Forum - Top